Sphingolipid control of cognitive functions in health and disease - Kalinichenko, Liubov; Gulbins, Erich; Kornhuber, Johannes; Müller, Christian P. (Progress in Lipid Research, 2022)
Cognitive processes, particularly learning and memory, are crucial brain mechanisms mediating the successful adaptation of individuals to constantly changing environmental conditions. Impairments in memory performance during neurodegenerative disorders or dementias affect life quality of patients as well as their relatives and careers, and thus have a severe socio-economic impact. The last decades have viewed learning and memory as predominantly protein-mediated process at the synapses of brain neurons. However, recent developments propose a principally new, lipid-based mechanism that regulates cognition. Thereby, crucial members of cell membranes, the sphingolipids, emerged to play an outstanding role in learning and memory. The most abundant brain sphingolipids, ceramides and gangliosides, dynamically shape the composition of protein carrying cellular membranes. This, in turn, regulates protein signaling through the membranes and overall neuronal plasticity. An imbalance in sphingolipid composition and disrupted dynamics significantly affect normal functioning of cells and results in the development of multiple psychiatric and neurological disorders with cognitive impairments. Ceramides and gangliosides interact with a plethora of molecular pathways determining de novo learning and memory, as well as pathogenic pathways of neurodegenerative disorders and dementias of various origins. Considering sphingolipids as a trigger mechanism for learning and memory under physiological and pathological conditions, a principally new class of lipid-based preventive and therapeutic approaches to target cognitive impairments and dementias is emerging.
CRIS-Team Scopus Importer:2022-04-29